OPTIMIZING THE POTENTIAL OF TOURISM VILLAGES FOR SUSTAINABLE DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Patra, Eka; Tukiran, Martinus (Universitas Pakuan, 2025)
ABSTRACTThis study aims to analyze the development of tourist villages in Bogor Regency in a comprehensive and integrated manner. The research data are in the form of articles related to the development of tourist areas. From the keyword search, 380 articles were obtained related to social participation in the development of tourist areas in Indonesia. The analysis of the research data used the systematic literature review (SLR) method. This study shows that tourist villages in Indonesia describe the objectives of the Sustainable Development Goals (SDGs), especially in reducing poverty, maintaining a sustainable environment and increasing income. By adapting strategies such as those implemented in Nglanggeran Village in Yogyakarta, Bogor Regency is likely to develop into a sustainable tourist village. Villages in Bogor Regency such as Sukajadi Village, Tugu Utara, and other surrounding villages are very attractive in terms of nature and culture. This also shows that tourism in these villages combines nature with the culture of the community. Through the distribution of agricultural crops, geological conditions and cultural tourism, they have the opportunity to improve the livelihoods of their own villagers, create new jobs and produce a better lifestyle for the surrounding population.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengembangan desa wisata di Kabupaten Bogor secara komprehensif dan terpadu. Data penelitian berupa artikel-artikel terkait dengan pengembangan kawasan wisata. Dari pencarian kata kunci diperoleh 380 artikel terkait partisipasi sosial dalam pengembangan kawasan pariwisata di Indonesia. Analisis data penelitian menggunakan metode systematic literature review (SLR). Penelitian ini menunjukkan bahwa desa wisata di Indonesia menjabarkan tujuan Sustainable Development Goals (SDGs), terutama dalam pengurangan kemiskinan, memelihara lingkungan yang berkelanjutan dan meningkatkan pendapatan. Dengan mengadaptasi strategi seperti yang diterapkan di Desa Nglanggeran di Yogyakarta, Kabupaten Bogor kemungkinan dapat berkembang menjadi desa wisata yang berkelanjutan. Desa-desa di Kabupaten Bogor seperti Desa Sukajadi, Tugu Utara, dan desa-desa di sekitarnya sangat menarik dari segi alam dan budaya. Hal ini juga menunjukkan bahwa pariwisata di desa-desa tersebut memadukan alam dengan budaya masyarakatnya. Melalui sebaran hasil pertanian, kondisi geologi, dan wisata budaya, mereka memiliki peluang untuk meningkatkan penghidupan penduduk desanya sendiri, menciptakan lapangan kerja baru, dan menghasilkan gaya hidup yang lebih baik bagi penduduk di sekitarnya.